La motricidad en el triatlón, otra mirada desde la física hacia la biomecánica (2021)
The article is a scientific research that addresses aspects of motor skills, supported by the fundamentals of biomechanics with a physical reasoning as sciences that study the movement of man in sports activity. The understanding of this knowledge increases the interest in physics in student-athletes of sports schools. To address this topic, a system of workshops supported with new information and telecommunications technologies (ICT) is proposed.